How parenting styles affect primary school students’ subjective well-being? The mediating role of self-concept and emotional intelligence - Gao, Tiantian; Li, Baoqian; Liang, Shuxian; Zhou, Wanmeng; Zhu, Xinyi; Bai, Lu; Li, Guoqiang (Frontiers in Psychology, 2024)
Purpose: To explore the relationship between parenting styles and self-concept, emotional intelligence, and subjective well-being among primary school students. Methods: In total, 1,683 students from 10 primary schools in Hangzhou, China, were surveyed using a simple random sampling method. Participants completed the Parenting Style Scale, the Self-Concept Scale, the Emotional Intelligence Scale, and the Subjective Well-Being Scale. Results: (1) Father's and mother's emotional warmth was significantly positively correlated with students' subjective wellbeing (r=0.513, P<0.01 and r=0.478, P<0.01, respectively). Father's and mother's rejection was significantly negatively correlated with students' subjective well-being (r=-0.257, P<0.01 and r=-0.285, P<0.01, respectively). Father's overprotection was significantly negatively correlated with students' subjective well-being (r=-0.178, P<0.01; r=-0.227, P<0.01). (2) Self-concept and emotional intelligence acted as chain mediators between father's and mother's emotional warmth and students' subjective well-being (0.337, 0.477 and 0.366, 0.520, respectively). Self-concept and emotional intelligence acted as chain mediators between father's and mother's rejection and students' subjective well-being (-0.590, -0.377 and -0.693, -0.460, respectively). Self-concept chainmediated between father's and mother's overprotection and students' subjective well-being (-0.380, -0.224 and -0.413, -0.264 respectively). Conclusion: Parenting styles can affect primary school student's subjective well-being both directly and through mediating effects. Self-concept and emotional intelligence partially mediate the impact of emotional warmth and rejection parenting styles, and fully mediate the impact of father's overprotective parenting on subjective well-being.